Comments on expenditure growth in line with potential GDP growth and the "Golden Rule": An assessment of the propositions of ECOFIN and a "Golden Rule" for public investment including educational spending. Supplement to the expertise "Stability by balanced growth" for the Group of the Progressive Alliance of Socialists & Democrats in the European Parliament by Torsten Niechoj - Henner Will (Hans-Böckler-Stiftung, Institut für Makroökonomie und Konjunkturforschung (IMK), 2011)
This comment for the European Parliament supplements the expertise by Niechoj (2011) on different proposals for the reform of the European Stability and Growth Pact. The comment focuses on two points: (1) Whether the proposition of the Economic and Financial Affairs Council (ECOFIN) is reasonable. This proposal aims at a modification of the former proposals in a way that - after having reached medium-term balanced budget objectives - governmental spending should grow only in line with potential GDP instead of actual GDP. It decreases pro-cyclicality and, therefore, should be implemented. (2) How a "Golden Rule" for public investment could be included into the pact. Against the background of sufficient available data, public net investment and net educational and research expenditures should be excluded from the regulation of the Stability and Growth Pact to increase long-run growth perspectives. – – Dieser Kommentar für das Europaparlament ergänzt die Stellungnahme zur Reform des europäischen Stabilitäts- und Wachstumspakts von Niechoj (2011). Dabei stehen zwei Gesichtspunkte im Zentrum des Interesses. Zum einen, ob der Vorschlag des Rats für Wirtschaft und Finanzen (ECOFIN) sinnvoll ist, bei Erreichen eines mittelfristig ausgeglichenen Haushalts Staatsausgaben nur noch mit der Rate des Produktionspotentials wachsen zu lassen. Dies verminderte das pro-zyklische Wirken von Staatsausgaben und ist daher zu begrüßen. Zum zweiten werden Überlegungen zu einer "Goldenen Regel" öffentlicher Investitionen diskutiert. Da eine ausreichende Datenlage gegeben ist, spricht alles dafür, (Netto-) Investitionen und wachstumsfördernde (Netto-) Ausgaben in den Bereichen Bildung und Forschung von den Bestimmungen des Stabilitäts- und Wachstumspaktes auszunehmen.
urn:nbn:de:101:1-201202285385
Keywords: 330